Strengthening Nationalism Values Post-Conflict in Society Southwest Aceh - *Rizal Fahmi; Ridayani Ridayani; Yuslijar Abdar (Universitas Syiah Kuala, 2021)
Strengthening the values of Nationalism in society is very important to do. This is especially true for communities that have been hit by prolonged conflict. This research was conducted based on the importance of strengthening the values of Nationalism in the people of Southwest Aceh after being hit by the conflict. The purpose of this study was to find out how the efforts made by the Southwest Aceh government in strengthening the values of Nationalism in the people of Southwest Aceh and to find out the inhibiting and supporting factors faced by the Southwest Aceh government to strengthen the values of nationalism in the people of Southwest Aceh. This study uses qualitative research methods, with data collection techniques through literature study, observation, interviews and documentation. The subjects in this study were village heads, village officials, traditional leaders, religious leaders and community leaders. The results showed that the form of strengthening the values of nationalism was carried out by socializing the values of nationalism through a cultural approach (ethnonationalism), a religious approach, commemorating national holidays, and mutual cooperation activities in society. Supporting factors in efforts to strengthen the values of nationalism in the people of Southwest Aceh are religious factors, the natural condition of the people of Southwest Aceh, and the character factor of the people of Southwest Aceh .Key Word: Values of Nationalism, Conflict